Hubungan Obesitas terhadap Mortalitas Pasien Gagal Jantung : Hasil Penelitian - Dewi, Annisa Oktrivia; Laariya, Tira Alfiani; Arliono, Tri Yunanto (Cermin Dunia Kedokteran, 2025)
Introduction: Obesity is a condition of excessive accumulation of body fat. Obesity has a greater risk of death from cardiovascular diseases. Heart failure is a clinical syndrome caused by structural and functional defects of the myocardium that result in impaired ventricular filling or blood ejection. This study was conducted to determine the relationship between obesity and mortality in heart failure patients at a teaching hospital in Yogyakarta. Methods: A cross-sectional quantitative study with an observational analytical research design from the secondary data from medical records of heart failure patients in January 2018–March 2024. Data was analyzed using Fisher’s exact test. Results: A total of 108 patients met the inclusion and exclusion criteria. Data analysis showed a p-value = 0.216 (>0.05). In this study, 61.1% of heart failure patients were male. The results showed that the mortality rate was higher in obese patients (11.1%) compared to non-obese patients (5.55%). Conclusion: There was no relationship between obesity and mortality among heart failure patients.